Pineal parenchymal tumour of intermediate differentiation: a rare case report - Rane, Deoyani P.; Patil, Ashwini Mane; Mulani, Jaahid B.; Tanawade, Prasad K.; Dhamne, Nilesh A.; Pawar, Suraj B. (International Journal of Research in Medical Sciences, 2024)
Pineal parenchymal tumours are erratic, accounting for <1% of all primary central nervous system tumours. It was first categorised by the WHO in 2000 as a pineal parenchymal tumour with an intermediate prognosis between pineocytoma and pineoblastoma. We reported a case of 38-year-old gentle man presented with chief complaints of headache and vomiting since 1 day. MRI brain showed a relatively well defined lesion epicentered at posterior aspect of third ventricle, extending and blocking Aqueduct of Sylvius leading to upstream dilatation of both lateral and third ventricles with periventricular ooze was observed. Excision of lesion was performed, histopathological diagnosis of pineal parenchymal tumours of intermediate differentiation (PPTID) was made, which was further confirmed on IHC. PPTID are enormously erratic tumour, and restricted data are available concerning their pathologic features and biologic behaviours causing interruption in making proper diagnosis and deciding an optimal treatment approach.